1985
DOI: 10.1093/infdis/152.4.716
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exoenzyme S in Infections with Pseudomonas aeruginosa

Abstract: To define the contribution of exoenzyme S to the pathogenesis of infections with Pseudomonas aeruginosa, we have compared the ability of an exoenzyme S-deficient mutant, 388 exs1::Tn1, and that of its exoenzyme S-producing parent to colonize and disseminate in burned mice infected with this organism. Both the exoenzyme S-deficient mutant and the parent strain proliferated in burned skin, but only the parent strain was able to effectively disseminate to blood and other tissues. The reduced ability of the mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0
2

Year Published

1988
1988
2004
2004

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 10 publications
1
73
0
2
Order By: Relevance
“…A variety of extracellular products appears to contribute to pathogenicity, including several proteases, cytotoxins, phospholipases, neuraminidase, capsular polysaccharides and lipopolysaccharides. A factor that is associated with the ability of P. aeruginosa to cross epithelial barriers and cause a blood-borne infection is the ADP-ribosyltransferase, exoenzyme S (Nicas and Iglewski, 1985;Nicas et al, 1985a).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of extracellular products appears to contribute to pathogenicity, including several proteases, cytotoxins, phospholipases, neuraminidase, capsular polysaccharides and lipopolysaccharides. A factor that is associated with the ability of P. aeruginosa to cross epithelial barriers and cause a blood-borne infection is the ADP-ribosyltransferase, exoenzyme S (Nicas and Iglewski, 1985;Nicas et al, 1985a).…”
Section: Introductionmentioning
confidence: 99%
“…One extracellular product, exoenzyme S, appears to be a major virulence determinant involved in the dissemination of P. aeruginosa from the initial site of colonization in the skin to the bloodstream of burned and infected animals (17,19). The ability to disseminate correlates to an increased incidence of fatal sepsis in these animals.…”
mentioning
confidence: 99%
“…The ability to disseminate correlates to an increased incidence of fatal sepsis in these animals. Passive administration of antiserum to exoenzyme S protects animals from sepsis but has no significant effect on the numbers of organisms recovered from the site of colonization (17). An exoenzyme S-deficient phenotype also correlates to a reduction in the amount and severity of tissue damage associated with P. aeruginosa chronic lung infections (35,36).…”
mentioning
confidence: 99%
“…In animal model studies comparing infections produced by parental P . aeruginosa strains with those produced by isogeneic mutants, singly deficient in exoenzyme S, it has been shown that infections with exoenzyme S-positive strains are much more severe (Nicas et al, 1985;Woods and Sokol, 1985): Phenotypic analysis of P . aeruginosa strains isolated from pulmonary infections in man showed that these strains produce significantly more exoenzyme S than strains isolated from other clinical sources such as urine or wound infections .…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa parent strains and isogeneic mutants singly deficient in either elastase or exoenzyme S. The parent strains were shown to be more virulent (Woods et al, 1982;Blackwood et al, 1983;Nicas et al, 1985;Woods and Sokol, 1985).…”
Section: Introductionmentioning
confidence: 99%